1983
DOI: 10.1139/e83-127
|View full text |Cite
|
Sign up to set email alerts
|

The greenschist facies of an Archean assemblage near Wawa, Ontario

Abstract: A stock of trondhjemite intrudes an Archean succession metamorphosed to the greenschist facies at Gutcher Lake, 30 km north of Wawa in Ontario. The stock is 4 km2 in plan and is partly enveloped by an aureole of epidote-amphibole hornfels up to 1 km wide. Within this aureole chlorite partly replaces biotite; chlorite, calcite, and quartz mantle hornblende and epidote; zoned amphibole has a rim of actinolite; and albite varies from 0 to 8% An. The stock has chlorite pseudomorphous after biotite, and feldspar is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…It is found that the increase of Fe 2+ /Fe 3+ ratio was accompanied by increasing the concentration of reducing agents such as H 2 and H 2 S in the fluids (Kerrich et al, 1977;Studemeister, 1983). The observed sulphides as main ore minerals in the Dungash alteration zones (more abundant in the carbonate-sericite and sericite zones) seem to reflect such phenomena.…”
Section: Discussionmentioning
confidence: 98%
“…It is found that the increase of Fe 2+ /Fe 3+ ratio was accompanied by increasing the concentration of reducing agents such as H 2 and H 2 S in the fluids (Kerrich et al, 1977;Studemeister, 1983). The observed sulphides as main ore minerals in the Dungash alteration zones (more abundant in the carbonate-sericite and sericite zones) seem to reflect such phenomena.…”
Section: Discussionmentioning
confidence: 98%
“…Morrison, 1979;Studemeister, 1983 ). The assemblage (albite + ) actinolite + epidote + quartz + sphene is indicative ofgreenschist facies conditions with T >~350°C and P >2 kbar (Winkler, 1967 ).…”
Section: Significance Qf Amygdale Mineral Assemblagesmentioning
confidence: 99%
“…All exhibit a metamorphic zonation similar to that observed in other granite-greenstone subprovinces, with greenschist-facies cores and amphibolite-facies zones developed marginal to large internal and external plutons (e.g., Ayres 1969, Studemeister 1983, McGill & Shrady 1986). In the Wawa area, Studemeister (1983Studemeister ( , 1985 suggested that pretectonic tonalite stocks produced greenschistfacies contact aureoles at 450-550°C and <2 kbar, with regional metamorphism affecting both the volcanic and plutonic rocks under conditions of 325-450°C and 2-3 kbar. In both the Shebandowan and Vermillion greenstone belts, regional metamorphism was associated with D 2 deformation, which affected Timiskaming-type metasedimentary and metavolcanic rocks.…”
Section: Quetico Subprovincementioning
confidence: 57%